How to prove
Follow Math Help Forum on Facebook and Google+
From what I see, it says "How to prove" then an icon indicating that you probably uploaded something but I'm unable to view it (I'm pretty sure I have the latest Adobe version...).
The image apparently says (ABC)⁻¹ = C⁻¹B⁻¹A⁻¹. This is because (ABC)(C⁻¹B⁻¹A⁻¹) = E (i.e., identity). The inverse element is unique, so since C⁻¹B⁻¹A⁻¹ is an inverse of ABC, it is the inverse.
before it, ensure all matrix are invertible first or its inverts don't exist causing it is wrong
(AB)-1 = B-1A-1
Then, put B=CD,
ie (ACD)-1 = (CD)-1A-1
Hence, prove completed
View Tag Cloud